Nowoczesne barwniki dla włókiennictwa. - Czajkowski, Wojciech (Wydawnictwo Politechniki Łódzkiej, 2006)
The textile industry which is stili the largest market within the coloration industry underwent serious changes in the last decades. The major objective of this textbook dedicated to chemists and colourists interested in synthesis and properties of dyes and pigments used in textile industry is to give information on the most important at present time application categories of colorants. All dye categories according to Colour Index classification are characterised with attempts to interpret their colouristic and fastness properties in terms of chemical structure of their molercules. Some important intermediates and their use in industrial practice of dyes syntheses are also indicated. The main attention is directed towards disperse dyes for polyester, reactive dyes for cellulose and pigments used in textile printing. Other dye categories such as direct, vat and sulphur dyes for cellulose, acid dyes for wool and polyamide and also cationic dyes for acrylic fibres are also reviewed and discussed. The principles of dyefibre interactions specific to dyed substrates during application processes are also given. Separate chapters are dedicated to perspective development of colouring matters in coming years and also to health and environmental safety measures during colorants handling and application.
Moders colorants for textile industry.
Red. serii : Wodziński, Piotr
Keywords: barwniki - zastosowanie przemysłowe; barwniki - chemia; włókiennictwo; przemysł włókienniczy; barwniki; dyes - industrial use; dyes - chemistry; textiles; textile industry; dyes